Wake Oscillator Model for Vortex-Induced Vibrations Predictions on Low Aspect Ratio Structures - Rahman, Mohd Asamudin A; Thiagarajan, Krish; Leggoe, Jeremy; Fitriadhy, Ahmad (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
A phenomenological Wake Oscillator Model (WOM) is studied to capture the coupling effects between the fluid and the structure. The Vortex-Induced Vibration (VIV) phenomenon is modelled to describe the motion imposed by the lift forces on the structure. The influence of the aspect ratio parameter (L/D) was introduced into the model to characterize the VIV phenomenon for finite cylinders. The proposed model captured the basic features of the VIV such as the amplitude of vibration, frequency, and lift coefficient by coupling the structural equation to the wake equation. Predictions of the WOM are discussed and compared with the experimental data in order to establish a relationship describing VIV as a factor of aspect ratios.